Ontogenetic Development of Olfactory Organs in Grass Shrimp Pandalus kessleri (Decapoda, Pandalidae) - Blinova, N.K.; Cherkashin, S.A. (Вестник зоологии, 2010)
The olfactory organ in decapod crustaceans is represented by the outer antennular flagellum with specialized sensilla called aesthetascs. Characteristic structures of the lateral antennular flagellum with olfactory setae in larvae, juveniles and adults of grass shrimp Pandalus kessleri Czerniavski, 1878 are described. Орган обоняния десятиногих ракообразных представлен наружными жгутами антеннул, с расположенными на них специализированными чувствительными щетинками — эстетасками. Описаны особенности строения латерального жгута антеннулы с обонятельными щетинками у личинок, молоди и половозрелых особей травяной креветки — Pandalus kessleri Czerniavski, 1878.